Effect of Foliar Spray with Cycocel, Salicylic Acid, and Silicon on Cucumber Vegetal Characteristics Grown under Salinity Stress and Greenhouse Conditions - سليمان, سوسن; دعيَس, ماهر; منصور, راما (Latakia University Journal -Biological Sciences Series, 2021)
The effect of foliar spray with cycocel, Salicylic acid, and Silicon on cucumber vegetal characteristics, grown under salinity stress and green house conditions, was studied, at research center of Al-Hennadi, related to Agriculture research center – Lattakia - Syria. The research concluded 14 treatments : 1-C, 2- SA 25, 3- SA50, 4- CCC400, 5-CCC600, 6-Si 100, 7- Si 200, 8-S, 9 –S+SA25, 10- S+SA50, 11-S+CCC400, 12-S+CCC600, 13-S+Si 100, 14-S+ Si 200. The results showed that foliar spray with Si and SA, reduced the negative effect of salinity, and enhanced inter node length, plant height, stem diameter, leaf number, leaf area/ plant (cm2), leaf area index, fresh and dry weight, and lateral shoot number when plants were irrigated with normal or saline water. The results showed as well that CCC treatment reduced inter node length, plant height, and increased stem diameter, fresh and dry weight, and lateral shoot number when plant were irrigated with normal water, but, when the plants were irrigated with saline water, CCC treatment increased stem diameter, leaf number, leaf area/ plant (cm2), leaf area index, fresh and dry weight, and lateral shoot number. The results indicated that SA, CCC, and Si could alleviate the harmful effect of salinity, with preference of Si which was more effective.